2022
DOI: 10.1098/rsos.211853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and cytotoxic properties of phenolic N -acylhydrazones: structure–activity relationship

Abstract: Cancer is still a relentless public health issue. Particularly, colorectal cancer is the third most prevalent cancer in men and the second in women. Moreover, cancer development and growth are associated with various cell disorders, such as oxidative stress and inflammation. The quest for efficient therapeutics is a challenging task, especially when it comes to achieving both cytotoxicity and selectivity. Herein, five series of phenolic N -acylhydrazones were synthesized and evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…These findings could be compared with our previous results regarding the cytotoxic activity of hydrazone compounds bearing a similar set of rings. [34] Namely, in our previous report, among 40 tested analogs, enhanced cytotoxic activity was observed for derivatives with the same B ring modification as in compounds b and d. These findings are partially consistent with the results obtained in this study since derivative j (same B-ring modification as d) was inactive toward tested cancer cells. Additionally, our previous report indicated that the presence of catechol moiety on the B ring is favorable for the activity, which was not observed in this study.…”
Section: Determination Of Cell Viabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…These findings could be compared with our previous results regarding the cytotoxic activity of hydrazone compounds bearing a similar set of rings. [34] Namely, in our previous report, among 40 tested analogs, enhanced cytotoxic activity was observed for derivatives with the same B ring modification as in compounds b and d. These findings are partially consistent with the results obtained in this study since derivative j (same B-ring modification as d) was inactive toward tested cancer cells. Additionally, our previous report indicated that the presence of catechol moiety on the B ring is favorable for the activity, which was not observed in this study.…”
Section: Determination Of Cell Viabilitysupporting
confidence: 91%
“…[57] The 1 H NMR and 13 The synthesis of the compounds a-n was performed using a previously reported method. [34] Here, the hydroxy benzohydrazide was mixed with equimolar amounts of the corresponding aromatic aldehyde in ethanol as solvent. The reaction mixture was heated to 80°C for 3 h. After the reaction completion (which was monitored by TLC), the formed precipitation was filtrated and washed with water.…”
Section: Discussionmentioning
confidence: 99%
“…This is advantageous for the hydrazone derivatives because it showed that they are more selective for cancer cells than commercially available medications. [ 81 ]…”
Section: N‐acylhydrazones As Anticancer Agentsmentioning
confidence: 99%
“…These substances have also demonstrated strong antioxidant properties in terms of scavenging free radicals. [14,15] The antioxidant activity may decrease or neutralize free radicals, preventing oxidative damage to cells. To avoid or lessen the effects of oxidative stress on cells, there is interest in developing synthetic antioxidant molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous members of this group of organic molecules function as intermediates in the synthesis of various heterocycles [8,9] and acyl hydrazones are reported as anticancer, [10] antimicrobial, [11] antiviral, [12] and anti‐inflammatory [13] agents. These substances have also demonstrated strong antioxidant properties in terms of scavenging free radicals [14,15] . The antioxidant activity may decrease or neutralize free radicals, preventing oxidative damage to cells.…”
Section: Introductionmentioning
confidence: 99%